2001
DOI: 10.1142/s021797920100735x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain on the Transport Properties of the Manganite

Abstract: The effect of strain on the resistivity and thermopower of ferromagnetic manganites has been examined based on the model that incorporates the electron-lattice interaction through the Jahn-Teller effect and an effective hopping determined by nearest neighbor spin-spin correlation of t 2g electrons. The metal insulator transition temperature associated with resistivity decreases with increase in strain. In the presence of large strain the system remains in the semiconducting state. Thermopower (S) is positive a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The field dependence of m c and e for different temperatures is reflected in the temperature dependence of the magnetoresistivity, which is shown in figure 6(b). With increasing magnetic field, the resistivity peak is suppressed considerably, exhibiting the tendency observed for colossal magnetoresistance as shown in several experimental measurements [3,19,22,31,32]. It can be seen here that the resistivity is independent of magnetic field in the high temperature paramagnetic phase.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The field dependence of m c and e for different temperatures is reflected in the temperature dependence of the magnetoresistivity, which is shown in figure 6(b). With increasing magnetic field, the resistivity peak is suppressed considerably, exhibiting the tendency observed for colossal magnetoresistance as shown in several experimental measurements [3,19,22,31,32]. It can be seen here that the resistivity is independent of magnetic field in the high temperature paramagnetic phase.…”
Section: Resultssupporting
confidence: 82%
“…It is observed that the resistivity becomes very high in the pure JT distorted phase near the Curie temperature of the manganite system separating the ferromagnetic metallic phase at low temperatures and the paramagnetic phase at higher temperatures, as observed in several experiments [12,31,32,34,35]. The resistivity attains a minimum value at the Curie temperature as the temperature is lowered, then increased slowly and is finally suppressed at still lower temperatures, indicating the ferromagnetic metallic phase of the system [12,[16][17][18][19]. With increasing magnetic field, the resistivity peak is suppressed considerably, exhibiting the tendency observed for the CMR effect in manganites.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation